(untitled) - Chung, Po (Australia, 2009)
This book, written by two practicing entrepreneurs, taps into the wealth of experience, the stories and the cases, from Asia and the West. More importantly, the authors accomplish what few books out there have, which is to really explore how to survive the first ten yards of a new company and thrive. From the dreamer who wants to launch a business to an MBA student or an executive, this book is for all of them. It addresses the critical factors that determine the success or failure of any new business venture
Keywords: Entrepreneurship,Doanh nhân